2014
DOI: 10.1039/c3dt52550c
|View full text |Cite
|
Sign up to set email alerts
|

Novel chiral (salen)Mn(iii) complexes containing a calix[4]arene unit in 1,3-alternate conformation as catalysts for enantioselective epoxidation reactions of (Z)-aryl alkenes

Abstract: Two new chiral calix[4]arene-salen ligands 1a,b, based on calix[4]arene platforms in 1,3-alternate conformation, have been prepared by a new general synthetic pathway. Their Mn(III) complexes, 3a,b have shown fairly good efficiency in the asymmetric epoxidation of styrene and substituted styrenes, whereas excellent catalytic activity and selectivity were observed with rigid bicyclic alkenes, namely 1,2-dihydro-naphthalene and substituted 2,2'-dimethyl-chromene. The higher catalytic properties of 3a may be ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In 2014 Sciotto et al reported the synthesis of two novel calix[4]arene–salen ligands 105a , b in 1,3-alternate conformation. Reaction of the salen ligands with appropriate metal acetate salt according to the Scheme 31 , led to the formation of uranyl and manganese complexes 106a , b–107a , b [ 70 ]. While Mn(III) complexes 107a , b have been used as catalysts for asymmetric epoxidation of styrene and substituted styrenes in the presence of NaClO as an oxygen donor and 4-phenylpyridine N -oxide (4-PPNO) as a coligand, their uranyl-(salen) derivatives 106a , b have been employed as models of the oxo-Mn(V)–(salen) oxidant species.…”
Section: Reviewmentioning
confidence: 99%
“…In 2014 Sciotto et al reported the synthesis of two novel calix[4]arene–salen ligands 105a , b in 1,3-alternate conformation. Reaction of the salen ligands with appropriate metal acetate salt according to the Scheme 31 , led to the formation of uranyl and manganese complexes 106a , b–107a , b [ 70 ]. While Mn(III) complexes 107a , b have been used as catalysts for asymmetric epoxidation of styrene and substituted styrenes in the presence of NaClO as an oxygen donor and 4-phenylpyridine N -oxide (4-PPNO) as a coligand, their uranyl-(salen) derivatives 106a , b have been employed as models of the oxo-Mn(V)–(salen) oxidant species.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the presence of a calix [4]arene cavity displaying inherent chirality has no effect on enantiodiscrimination. In order to increase stereoinduction, the same group has bridged two distal phenolic units of a calix [4]arene in its 1,3-alternate conformation with an enantiopure salen unit having various degrees of flexibility owing to spacers of different chain length that link the coordinating salen unit to the calix [4]arene platform (Figure 1) [34]. As for the previous catalytic systems, NaClO was used as oxygen donor and 4-phenylpyridine N-oxide (4-PPNO) as co-ligand (Scheme 12).…”
Section: Chiral Cavity-shaped Ligands Derived From Calixarenesmentioning
confidence: 99%
“…The catalyst 30 was recycled four times without loss of either activity or enantioselectivity. Tomaselli, Sciotto et al . reported the synthesis of two original chiral calixarene‐salen ligands in a 1,3‐alternate conformation linked to a salen moiety by spacers of different lengths.…”
Section: Macrocyclic Salen Complexesmentioning
confidence: 99%
“…[72] The catalyst 30 was recycled four times without loss of either activity or enantioselectivity. Tomaselli, Sciotto et al [73] reported the synthesis of two original chiral calix [4] arenesalen ligands in a 1,3-alternate conformation linked to a salen moiety by spacers of different lengths. Their Mn complexes were used to catalyze the asymmetric epoxidation of several alkenes (12 examples) with the complex possessing the more rigid structure leading to higher ee values.…”
Section: Macrocyclic Salen Complexesmentioning
confidence: 99%